PENGARUH TEMAN SEBAYA DAN PEMANFAATAN MEDIA MASSA TERHADAP KEJADIAN PERILAKU SEKSUAL PRANIKAH REMAJA KELAS X - M Hasinuddin (NHM PRESS, 2019)
Premarital sexual behavior is a serious problem and is increasing every year. With an average occurrence of 105 events in premarital seksual behavior in 2016. The results of a preliminary study occurred as many as 20 events in premarital sexual behavior in SMKN 1 Bangkalan. The case of intercourse was recorded as a case with the highest number of cases of abuse. The purpose of this study is to analyze the influence of peers and the role of mass media on premarital sexual behavior of adolescents class X in SMKN 1 Bangkalan. This research method was analytic with cross sectional approach. The independent variable of peer influence and mass media while the dependent variable of premarital sexual behavior of adolescent. The population was 75 respondents, the sample is 63 respondents. The sampling used simple random sampling, the instrument used is questionnaire. Statistic test used by Somers'd with significance value α 0,05. The results showed that peer influence showed almost all 55 people (87%) had highrisk peer influence. The results of the stereotype Somers'd concluded there was influence of peers against the incidence of teenage sexual behavior in SMKN 1 Bangkalan. While the utilization of the mass media and a half of the respondents have a good utilization rate by as much as 38 people (60%). Based on statistic test of Somers'd concluded there was influence of mass media utilization level to the occurrence of adolescent sexual behavior in SMKN 1 Bangkalan. The efforts to handle or prevent premarital sexual behavior is by educating and protecting teenagers. The parents should be given an adequate knowledge of particular sexual behaviors, premarital counseling by giving due importance to teens in interacting with friends and receiving more information in the mass media.